Impact of natural and social environmental factors on building energy consumption: Based on bibliometrics - Li, Lingyan; Sun, Wanming; Hu, Wei; Sun, Yongkai (Journal of Building Engineering, 2021)
Currently, building energy consumption is increasing, thereby exacerbating various issues, including climate change and environmental pollution. However, current building energy consumption research is limited to a unilateral review regarding the impact of environmental factors from natural or social aspects. To broaden this research, we first used VOS Viewer software to analyze high-frequency keywords appearing in relevant studies to determine the specific environmental factors that affect building energy consumption. Then, according to the visualization results, we reviewed the internal influence mechanism of environmental factors that affect building energy consumption from both natural and social perspectives. Based on these results, we constructed a new environment-people-building framework to help researchers explain the relationship between natural and social environmental factors. The results show that interdisciplinary interactive research that combines the natural and social environments from a dual perspective will attract new research ideas. Further, the framework provides help in systematically clarifying the mechanism of different factors affecting building energy consumption, which will help engineers and policymakers identify applicable designs and operation measures to reduce building energy consumption. •The evolution of research on the impact factors of building energy consumption was analyzed using VOS Viewer software.•The impact factors on building energy consumption from the perspective of the natural and social environment were explored.•A environment-human-building framework was established to annotation the formation mechanism of building energy consumption.•Research gaps regarding the impact of environmental factors on building energy consumption were identified.